El Salvador : Third Review under the stand-by arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director.. (IMF Staff Country Reports; Country Report ;, 2011)
The IMF staff report for the third review under the Stand-By arrangement with the officials of El Salvador on economic developments and policies. Developments from the second review are outlined. Discussions on the policy adjustments needed to keep the key objectives of the program for 2011 and 2012 have been explained. Revenue administration, treasury single account (TSA), medium-term expenditure framework (MTEF), and budget reforms are used to strengthen the fiscal consolidation strategy. Lender-of-last-resort (LOLR) facility has been set up to improve liquidity defenses.